An Exhaustive Review on a Solar Still Coupled with a Flat Plate Collector - Ahmadreza Ayoobi; Mahdi Ramezanizadeh (International Journal of Photoenergy)
In recent years, producing energy and potable water has become a contemporaneous issue in all areas, especially in rural and remote areas. It is due to the limitation of fossil fuels in generating energy and the daily increase of potable water topic pollution due to various development activities in the industries. Gradually, the use of renewable energies has been suggested as far as humans focus on using these energies in various activities, which is gratis and accessible in more areas without having negative anthropogenic hazards. Solar radiation has an important position in renewable energies and has played a significant role in the desalination process due to the convenience in applying and abundance in the areas with potable water shortages. However, one of the active solar stills is the coupling of conventional solar still with a flat plate collector. In this type, a flat plate collector is used to raise the temperature of saline water which increases the productivity. In this research, the solar still coupled with a flat plate collector is reviewed as the active solar still and the affecting parameters on its performance and efficiency are discussed. First, a summary of working research and their research of flat plate collectors is reviewed to be more familiar with flat plate collectors, their details, and technology. Then, solar still coupled with a flat plate collector is extensively reviewed and discussed in detail. Four types of studies on solar still coupled with a flat plate collector were done, including energy analysis, exergy analysis, economic analysis, and productivity evaluation.